The Role of Energy Policy in Emissions from Electricity Generation in Latin America - Zilio, Mariana I. (2012)
In the frame of the debate on the relationship between GDP and greenhouse gases emissions, the objective of this paper is to analyze the link between carbon dioxide emissions from electricity generation and per capita GDP for a sample of the ninemost developed Latin American countries. From the results of this analysis it is possible to conclude that, in the case of these countries, energy policy decisions may be more powerful than per capita GDP to define emissions from electricity generation. Therefore, the use of these emissions in the validation of the Carbon Kuznets Curvehypothesis could be questioned